Greek Tragedy or Theatre of the Absurd? Montes Huidobro's Oscuro total - Zatlin, Phyllis (Latin American Theatre Review, 2004)
In his groundbreaking study on the Theatre of the Absurd, Martin Esslin suggests a connection between Greek tragedy and the twentieth-century movement. The connection is made explicit in Matías Montes Huidobro's Oscuro total. The play has as its pre-text a real episode: the 1989 killing, in California, of José and Mary Louise ("Kitty") Menéndez by their sons Lyle and Erik. Montes Huidobro takes the horrifying, real tale of a dysfunctional family in the United States and re-creates it as a powerful meld of classic Greek tragedy and contemporary absurdist theatre of cruelty. (PZ)